2016
DOI: 10.2214/ajr.15.15028
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Tensor Imaging of Thigh Muscles in Duchenne Muscular Dystrophy: Correlation of Apparent Diffusion Coefficient and Fractional Anisotropy Values With Fatty Infiltration

Abstract: Damage to the thigh muscles in patients with DMD can be detected by ADC and FA values using DTI. DTI can be used to assess the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…In a similar way, DTI has been used to measure the organization of muscle, which also consists of longitudinally oriented groups of fibers. Early work on DTI in muscular dystrophy indicates that perturbations in fiber organization can be detected in DMD and limb‐girdle muscular dystrophies …”
Section: Evaluating Diffusivity and Fiber Orientation In Musclementioning
confidence: 99%
See 1 more Smart Citation
“…In a similar way, DTI has been used to measure the organization of muscle, which also consists of longitudinally oriented groups of fibers. Early work on DTI in muscular dystrophy indicates that perturbations in fiber organization can be detected in DMD and limb‐girdle muscular dystrophies …”
Section: Evaluating Diffusivity and Fiber Orientation In Musclementioning
confidence: 99%
“…Early work on DTI in muscular dystrophy indicates that perturbations in fiber organization can be detected in DMD and limb-girdle muscular dystrophies. [73][74][75]…”
Section: Evaluating Diffusivity and Fiber Orientation In Musclementioning
confidence: 99%
“…Quantitative MRI (qMRI) techniques (in particular fat quantification with Dixon sequences) have been applied mostly to dystrophinopathies (Duchenne and Becker muscular dystrophy), while very few or no data are available for other, more rare, muscular inherited disorders like LGMDs …”
mentioning
confidence: 99%
“…12 Quantitative MRI (qMRI) techniques (in particular fat quantification with Dixon sequences) have been applied mostly to dystrophinopathies (Duchenne and Becker muscular dystrophy), while very few or no data are available for other, more rare, muscular inherited disorders like LGMDs. 5,11,[13][14][15][16][17] In this study, we applied the above-mentioned qMRI techniques to patients affected by LGMD2A and LGMD2B, which represent the most frequent forms of LGMD in the Italian population. 18 The aims of this work were (i) the quantification of the structural modifications occurring in the thigh muscles, (ii) the identification of (potentially) different patterns of degeneration between the 2 disorders and in different muscular compartments of the thigh, (iii) the identification of MR-derived disease markers correlating with clinical parameters of muscular strength and function.…”
mentioning
confidence: 99%
“…Going back to early morphologic papers and extending to correlative MRI‐histopathologic studies, fat‐infiltration has not been observed at similar levels in GRMD dogs. Furthermore, clinical studies demonstrated different fractional anisotropy (FA), apparent diffusion coefficient (ADC), and mean diffusivity (MD) measurements between DMD and healthy patients. FA is negatively correlated with muscle strength but positively correlated with age and fat infiltration, while ADC is positively correlated with muscle strength but negatively correlated with age and fat infiltration .…”
mentioning
confidence: 99%